HAMKA: From the First Pancasila to the Integrity of Bhineka Tunggal Ika in Indonesia - Ramadan, Risky Aulya; Pujiyaturrahmi, Pujiyaturrahmi (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2024)
This problem begins with the fading of understanding and application of Pancasila values as a way of life in society, nation and state, especially the first principle in Indonesia. This has led to the emergence of various separatist movements that want to separate themselves from the Republic of Indonesia and groups that do not want to respect the red and white flag, sing the Indonesia Raya song and so on. HAMKA said that it was from the first precept of “Belief in One God” that everything began, from that precept as a vein of Pancasila, according to him if the Indonesian people really understood the meaning of this first precept, the next precepts would be well preserved and Bhineka Tunggal Ika was created. This article uses qualitative research methods and this type of research is literature. The primary data of this research is obtained through reading HAMKA's works while secondary data is obtained from books and journals related to Pancasila and Unity in Diversity. This article uses document study as the basis for data collection. This article finds HAMKA's wise attitude in maintaining the integrity of Bhineka Tunggal Ika, by giving a moderate response to Bung Karno's speech so as not to cause hatred and division and the proposal to hold halal bi halal Eid al Fitri and Christmas are equalized. This article has implications for strengthening the motto of Unity in Diversity in Indonesia